Candidate genes in ocular dominance plasticity - Rietman, M. L.; Sommeijer, Jean-Pierre; Levelt, Christiaan N.; Heimel, J. A. (Frontiers in Neuroscience, 2012)
The objective of this study was to identify new candidate genes involved in experience-dependent plasticity. To this aim, we combined previously obtained data from recombinant inbred BXD strains on ocular dominance (OD) plasticity and gene expression levels in the neocortex. We validated our approach using a list of genes which alter OD plasticity when inactivated. The expression levels of one fifth of these genes correlated with the amount of OD plasticity. Moreover, the two genes with the highest relative inter-strain differences were among the correlated genes. This suggests that correlation between gene expression levels and OD plasticity is indeed likely to point to genes with a causal role in modulating or generating plasticity in the visual cortex. After this validation on known plasticity genes, we identified new candidate genes by a multi-step approach. First, a list was compiled of all genes of which the expression level in BXD strains correlate with the amount of OD plasticity. To narrow this list to the more promising candidates, we took its cross-section with a list of genes co-regulated with the sensitive period for OD plasticity and a list of genes associated with pathways implicated in OD plasticity. This analysis resulted in a list of 32 candidate genes. The list contained unproven, but not surprising, candidates, such as the genes for IGF-1, NCAM1, NOGO-A, the gamma2 subunit of the GABA(A) receptor, acetylcholine esterase and the catalytic subunit of cAMP-dependent protein kinase A. This was indicative of the viability of our approach, but more interesting were the novel candidate genes: Akap7, Akt1, Camk2d, Cckbr, Cd44, Crim1, Ctdsp2, Dnajc5, Gnai1, Itpka, Mapk8, Nbea, Nfatc3, Nlk, Npy5r, Phf21a, Phip, Ppm1l, Ppp1r1b, Rbbp4, Slc1a3, Slit2, Socs2, Spock3, St8sia1, Zfp207. The possible role of some of these candidates is discussed in the article.